DIGITALIZATION OF THE HIGHER EDUCATION SYSTEM: ANALYSIS OF THE CURRENT LEVEL OF ACHIEVEMENTS IN COMBATING CORRUPTION - Farrukh Gaybullaev (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article analyzes the role of digitalization in the higher education system in preventing corruption.